Skeletal Dysplasias: Growing Therapy for Growing Bones - Jelin, Angie C.; O'Hare, Elizabeth; Blakemore, Karin; Jelin, Eric B.; Valle, David; Hoover-Fong, Julie (Frontiers in Pharmacology, 2017)
Skeletal dysplasias represent a large and diverse group of rare conditions affecting collagen and bone. They can be clinically classified based on radiographic and physical features, and many can be further defined at a molecular level . Early diagnosis is critical to proper medical management including pharmacologic treatment when available. Patients with severe skeletal dysplasias often have small chests with respiratory insufficiency or airway obstruction and require immediate intubation after birth. Thereafter a variety of orthopedic, neurosurgical, pulmonary, otolaryngology interventions may be needed. In terms of definitive treatment for skeletal dysplasias, there are few pharmacotherapeutic options available for the majority of these conditions. We sought to describe therapies that are currently available or under investigation for skeletal dysplasias.